Sayembara Misuhi Pandemi: Wujud Katarsis dalam Kreativitas Kebahasaan di Tengah Gelombang Pandemi Covid-19 - Prakoso, Imam (Kamaya: Jurnal Ilmu Agama, 2025)
This study examines the variations in Javanese swear words created in a competition titled "Sayembara Misuhi Pandemi" initiated by the Jawasastra Community. Furthermore, this study aims to examine the meaning and factors behind the emergence of these curses. The data in this study were taken from video posts on Instagram using the hashtag #misuhipandemi, which was used to identify participants in the "Misuhi Pandemic" competition. Next, the data were classified based on their linguistic markers. Data analysis was conducted using semantic descriptions of the lingual markers in the form of words and describing the sentence contexts within the curses to understand the meaning and factors behind their emergence. The analysis results show that the uniqueness of this competition is reflected in the variety of curse words directed at the COVID-19 pandemic. The curse words that emerged as curses regarding the COVID-19 pandemic are associated with nouns, verbs, and adjectives or states. When examined by factors, swearing during the COVID-19 pandemic is caused by boredom from prolonged periods at home, anger due to limited interaction with others, anger due to economic factors, and anger at society's indifference during the COVID-19 pandemic.